Experimental orthotopic prostate tumor in nude mice: techniques for local cell inoculation and three-dimensional ultrasound monitoring - Saar, Matthias; Grobholz, Rainer (Urologic oncology, 2012)
Objectives: Orthotopic prostate cancer models are of great importance for cancer research. Orthotopic models in mice have been described previously. However, these studies lack a detailed methodological description and fail to define standards for local cell inoculation. Herein, we studied the effect of different protocols on tumor growth and report for the first time the use of high resolution ultrasound for monitoring of tumor growth. Materials and methods: Orthotopic inoculation of DU 145 MN1 prostate cancer cells was performed in 30 nude mice varying (1) the amount of cells (5 × 105 vs. 5 × 104), (2) the number of puncture sites, and (3) the addition of matrigel. Surgical complications such as recoil of cells through the injection canal and rupture of the prostatic capsule were monitored. Animals were tracked by ultrasound imaging after 4, 5, and 6 weeks. Autopsy and histology confirmed local tumor growth. Results: A take rate of 27/30 (90%) was observed. Growth of orthotopic prostate tumors was increased after inoculation of a large amount of cells under the capsule of 1 dorsal prostate lobe, but inoculation of small amounts of cells still induced local tumors. Noninvasive ultrasound examination allowed to identify orthotopic tumor formation and to monitor tumor growth in vivo. Addition of matrigel did not accelerate tumor growth. Complications like recoil (6.8%) or rupture of the prostate capsule (1.4%) were rare. Conclusions: Inoculation of DU 145 MN1 cells under the prostate capsule with a defined procedure results in very high take rates. Ultrasound screening is feasible to repetitively monitor tumor growth.
Gesehen am 30.05.2018